Synthesis of Research on the Reproductive Biology of Queen Conch (Aliger gigas): Toward the Goals of Sustainable Fisheries and Species Conservation - Stoner, Allan W.; Appeldoorn, Richard S. (Reviews in fisheries science, 2022)
The queen conch (Aliger gigas) is a culturally and economically important molluskan fishery resource in the Caribbean region showing increasing signs of over harvest. Shallow-water distribution and large size facilitate capture, and internal fertilization and density-dependent reproduction make managing for reproductive biology critical to stock rehabilitation. In fact, the natural lifetime fecundity of conch is very high but most fisheries in the region harvest conch before even a small fraction of that reproductive potential can be attained. The goal of this review is to provide an up-to-date synthesis of the vast research literature on queen conch biology (spanning >60 years) and to discuss how knowledge of reproduction in conch can help to guide field surveys, fishery management decisions, and stock recovery projects. The review covers the subjects of anatomy, maturation and fecundity as they relate to conch age and size, reproductive behavior including migrations, seasonality, mating, and egg-laying, and the influences of both environmental and demographic variables on reproductive potential. Successes and failures under different forms of management practice are discussed as they relate to reproductive biology and recommendations are made for future research and fishery management alternatives. Successful management will require multiple regulatory approaches.